‘Individualism’ and ‘collectivism’ in collective labour law - Bogg, A (Oxford University Press, 2017)
This article examines the concepts of ‘individualism’ and ‘collectivism’ in collective labour law. A popular critique of freedom of association norms characterises such norms as ‘individualist’ or ‘individualistic’. This individualist bias undermines the institutions of collective labour relations. The ‘individualist’ critique is often coupled with the development of an alternative positive account of collective labour law that is based upon a foundation of ‘collectivism’. ‘Collectivist’ labour law encompasses a concern for collective or group rights, rather than rights for individuals; it affirms collective values; and the metric of legitimacy of a legal regime of freedom of association is the extent to which it supports collective bargaining through independent trade unions. On this conventional approach, ‘individualism’ and ‘collectivism’ stand in opposition to each other. This article argues against this dichotomous understanding of ‘individualism’ and ‘collectivism’. A comparative perspective on the ‘right to organise’ supports the view that individual and collective rights can stand in a complementary relation to each other. Furthermore, the union’s right to exclude may sometimes legitimately yield to competing individual rights, such as the right not to be subjected to unjust discriminatory treatment. The important task for labour lawyers is to identify an effective combination of collective and individual rights in order to promote just and decent outcomes in the workplace.